Do the dark triad personality traits buffer against stress? a study among students of higher education in Malaysia. - Nurhamiza Mumin @ Osman (Secholian Publication, 2021)
Stress and anxiety are prominent mental-health issues among students worldwide. The current students of higher education are digital natives who are accustomed to immediate feedback and instant gratifications. Therefore, they are susceptible to stress differently compared to the previous generations. Given the seriousness of the stress-related issue in higher education, this study was conducted to examine the role of dark triad personality (Machiavellianism, narcissism, and psychopathy) as a buffer against stress. The socially aversive and interpersonally adaptive nature of dark personality traits makes them ideal candidates for further investigation on the influence of personality on stress. The Dark Triad Dirty Dozen and Perceived Stress Scale were used to collect data from 549 respondents. Data were analyzed in two stages using Partial-Least Square-Structural Equation Modelling (PLS-SEM). The study revealed that the only dark triad personality that has a role in the increased level of stress is psychopathy. However, the finding was significant among men but not for women. The current study cannot statistically account for the population of different institutional settings since it only captured samples within higher education institutions in Malaysia. Therefore, future research should be extended to wider populations that cover individuals in certain practices or those with a leadership position in any profession.